The Silent Killer of Projects: How to Manage Scope’ Creep - Alwossabee, Abdulatif; Alharthy, Amjad (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
According to PMI’s 2018 Pulse of the Profession® 52% of projects completed in 2018 experienced scope creep or uncontrolled changes to the project’s scope—up from 43% five years prior. This paper delves into the concept of scope creep, examining its primary factors and adverse effects. Furthermore, it offers valuable recommendations and guidelines on how to proactively anticipate, plan, and manage scope creep.